The inhibitory effects of spice essential oils and rapidly prediction on the growth of Clostridium perfringens in cooked chicken breast. (July 2020) - Zhu, Yaodi; Ma, Yangyang; Zhang, Jiaye; Li, Miaoyun; Yan, Longgang; Zhao, Gaiming; Liu, Yanxia; Zhang, Yanyan
Abstract: In this study, the effects of spices essential oils on the growth of C. perfringens were investigated. The in vitro inhibitory activities and minimum inhibitory concentrations (MIC) of different essential oils on C. perfringens were determined using the Oxford cup and two-fold dilution method. And two models (the parameter-adjusted Gompertz kinetic model, and least square support vector machine (LS-SVM) model) were used to rapidly predict the relative growth/survival of C. perfringens in cooked chicken breast under different essential oil concentrations. The results indicated that cinnamon essential oil exhibited a notable inhibitory effect on C. perfringens in vitro. Moreover, cinnamon essential oil had the lowest inhibitory concentration, and the growth of C. perfringens ceased completely at 19.12 mg/mL and 22.72 mg/mL, respectively. By comparing, the LS-SVM model is the optimum model. The prediction accuracy of the LS-SVM model was greater than 0.99, and the degree of fitting is higher than adjusted Gompertz kinetic model. The results present illustrate that the model using LS-SVM has high prediction accuracy and can be employed to predict the number of C. perfringens under different essential oils. This work could contribute to control and rapid assessment of food safety hazards of C. perfringens during meat processing. Highlights: The effect of spices essential oils on the survival of C. perfringens were studied. The in vitro inhibitory activities and MIC of spices essential oils were studied. The cinnamon essential oil exhibited a notable inhibitory effect on C. perfringens . The rapidly prediction model of the survival of C. perfringens is proposed. LS-SVM is the optimal model for predicting the survival of C. perfringens .